A role for EMT in CD73 regulation in breast cancer. (31st December 2022) - Hasmim, Meriem; Berchem, Guy; Janji, Bassam
ABSTRACT: CD73 is an emerging target in cancer due to its role in generating adenosine, a potent immunosuppressor. We found that SNAI1, a driver of epithelial-to-mesenchymal transition (EMT), upregulates CD73 in triple negative breast cancer cells. Here, we discuss the relevance of improving CD73-based therapy by combining with inhibitors of EMT.